Uniquely Human: The Ethics of the Imago Dei in Genesis 1–11 - Schüle, Andreas (Toronto journal of theology, 2011)
Wentzel van Huyssteen proposes an intriguing reinterpretation of the biblical symbol of the imago Dei, according to which the purpose of humankind as created in the image of God is "to set forth the presence of God in this world." It is not one particular aspect of human life that is associated with the imago Dei, such as rationality and reason; rather, van Huyssteen invites us to consider the complexity of human life in its evolutionary, biological, social, and ethical dimensions as an expression of the imago Dei. This article explores how his ideas resonate with a historical-critical reading of the pertinent passages in Genesis 1-11. It has often been overlooked that the imago Dei in primeval history is deeply embedded in the priestly account of how life—human and other—is created and how it unfolds. As such, the imago Dei appears in contexts that describe the relationships between humans and animals, men and women, parents and children, and, in a general ethical sense, between neighbours. Humans are called images of God because they are capable of creating, shaping, and changing the networks of relation that connect them with each other and with the rest of creation. It is in these networks that humans fill the world with the kind of life that sets forth divine presence in the world.